Trials Of Civilians Before Military Courts: Subversion Of Justice - Anyebe, Peter Ademu (NIU Journal of Humanities; Vol 7 No 1 (2022): NIU Journal of Humanities, Vol. 7 No. 1, March 2022DO - 10.58709/niujhu.v7i1.1393, 2022)
The use of military courts to try civilians contravenes international law. This paper examines the major concerns about military courtâ€™s jurisdiction over civilians. It is the argument of the paper that military courts sometimes are used to prosecute or determine the rights of civilians thereby allowing for procedures that deviate from standards applied by regular civilian courts. Furthermore, the paper argues that civilians tried before military courts have their rights routinely violated. the paper concludes that there is international consensus that trials of civilians by military courts contravenes the non-derogable right to a fair trial by a competent, independent and impartial court to the extent that they violate rights guaranteed by universal declaration of human rights and the united nations international covenant on civil and  political rights. Keywords: civilians, court-martial, fair trial, military courts, military tribunals, justice, military justice, rights